2022
DOI: 10.1039/d2gc00304j
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient doping of titanium dioxide with sulfur using disulfide-linked macrocycles for hydrogen production under visible light

Abstract: Doping sulfur into TiO2 can narrow the bandgap of the native TiO2, offering an efficient way to improve its photocatalytic efficiency and extend its absorption from the ultraviolet to the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…TEM images reveal that the distribution of Pt particles on the surface of the NA−TiO 2 (2.5 wt %) material was uniform, with an approximate size of 3 nm (Figure 1E). As shown in High Resolution Transmission Electron Microscope (HRTEM) (Figure 1F), the lattice spacing of Pt nanoparticles was 0.196 nm, corresponding to the Pt (200) plane, consistent with the crystal plane of Pt particles [10d,11] . Moreover, High‐Angle Annular Dark Field (HAADF) (Figure 1G) elemental mapping demonstrated that Ti, O, C, and Pt elements were evenly distributed throughout the hybrid material Pt (0.3 wt %)/NA<C‐<TiO 2 (2.5 wt %).…”
Section: Resultssupporting
confidence: 65%
“…TEM images reveal that the distribution of Pt particles on the surface of the NA−TiO 2 (2.5 wt %) material was uniform, with an approximate size of 3 nm (Figure 1E). As shown in High Resolution Transmission Electron Microscope (HRTEM) (Figure 1F), the lattice spacing of Pt nanoparticles was 0.196 nm, corresponding to the Pt (200) plane, consistent with the crystal plane of Pt particles [10d,11] . Moreover, High‐Angle Annular Dark Field (HAADF) (Figure 1G) elemental mapping demonstrated that Ti, O, C, and Pt elements were evenly distributed throughout the hybrid material Pt (0.3 wt %)/NA<C‐<TiO 2 (2.5 wt %).…”
Section: Resultssupporting
confidence: 65%
“…Although previous reports on the combination of CSSH and TiO 2 are limited, the tridentate bond between the S atom and TiO 2 was predicted by DFT calculation, 70 and current synthesis technology can also achieve doping of sulfur on the surface of TiO 2 . 71 The bonding type of -CSSH on the TiO 2 surface with different substituted groups is also an interesting topic, which we will consider in future investigations.…”
Section: Photovoltaic Properties In Dsscsmentioning
confidence: 99%
“…Carbon doping can increase the TiO2 conductivity and enhance its charge transfer properties 21 . Sulphur doping can modify the TiO 2 surface to improve its stability and prevent photo corrosion 22 …”
Section: Introductionmentioning
confidence: 99%
“…21 Sulphur doping can modify the TiO 2 surface to improve its stability and prevent photo corrosion. 22 Experimentally, the changes in optical absorption induced by ion doping are detected by optical spectroscopy, 23,24 while the location of the dopant can be determined by XAS. 25,26 In photocatalysis, bulk ion doping affects optical absorption and surface atom arrangement.…”
Section: Introductionmentioning
confidence: 99%